Dynamic analysis and modelling of a Francis hydro-energy generation system in the load rejection transient - Li, H.; Chen, Diyi; Zhang, Xinguang; Wu, Yong Hong (The Institution of Engineering & Technology, 2016)
©The Institution of Engineering and Technology 2016.In this study, the authors propose a novel non-linear mathematical model of a hydro-energy generation system in the load rejection transient considering the elastic water hammer-impact of the penstock and the non-linear characteristics of the generator. More specifically, six dynamic transfer coefficients of the hydro-turbine are introduced to the generation system. Furthermore, the dynamic behaviours of the system are investigated using bifurcation diagrams and time waveforms from the point of engineering. Finally, these methods and analytical results will supply some principles for designing and running a hydropower station.